Teknologi Informasi dalam Pemasaran guna Meningkatkan Usaha Mikro Kecil dan Menegah di Desa Cicalengka Kecamatan Pagedangan Kabupaten Tangerang - Sulistiani, Sinta; Andalusi, Ratih; Wulansari, Retno (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The growth of digital technology offers great potential for supporting Micro, Small, and Medium Enterprises (MSMEs), especially in rural regions where digital literacy remains limited. Many business actors in these areas struggle to utilize information technology effectively for marketing purposes. To respond to this challenge, a community service program (PKM) titled